Characterization of Novel Multifunctional Xylanase from Rumen Metagenome and Its Effects on In Vitro Microbial Fermentation of Wheat Straw - Moguang Zhang; Qinghua Qiu; Xianghui Zhao; Kehui Ouyang; Chanjuan Liu (Fermentation)
This study investigated the characterization of a novel multifunctional enzyme, RuXyn394, derived from the metagenome of beef cattle rumen, and its impact on the in vitro microbial fermentation of wheat straw. RuXyn394, a member of the glycosyl hydrolase 11 family, displayed optimal activity under diverse pH and temperature conditions: xylanase at pH 5.5 and 50 °C, acetyl esterase at pH 6.5 and 60 °C, exoglucanase at pH 7.0 and 50 °C, and endoglucanase at pH 6.0 and 50 °C. The enzyme’s xylanase, endoglucanase, and exoglucanase activities exhibited remarkable pH stability across the range of pH 3–8 and maintained a relatively stable performance at temperatures from 20 to 50 °C, 20 to 60 °C, and 20 to 70 °C, respectively. The xylanase function, with the highest kcat/Km ratio, was identified as the predominant activity of RuXyn394. The enzyme’s various functions responded uniquely to metal ions; notably, the addition of 5 mM K+ significantly boosted the activities of xylanase, exoglucanase, and endoglucanase by 55.5%, 53.5%, and 16.4%, respectively, without affecting its acetyl esterase activity. Over the course of three time points (30 min, 60 min, 120 min), the degradation products of wheat straw xylan, including xylopentaose, xylotetraose, xylotriose, xylobiose, xylose, and total xylooligosaccharides, constituted an average of 18.4%, 33.7%, 20.6%, 22.9%, 4.3%, and 95.7% of the total products, respectively. RuXyn394 effectively hydrolyzed wheat straw, resulting in augmented volatile fatty acid production and ammonia-N levels during in vitro microbial fermentation. These findings indicate the potential of RuXyn394 as a novel and highly efficient enzyme preparation, offering promising prospects for the valorization of wheat straw, an agricultural by-product, in ruminant diets.